Empowered : unleash your employees, energize your customers, transform your business. - Bernoff, Josh, ....-; Schadler, Ted, ....- (Boston : Harvard Business Review Press, 2010)
Are You EMPOWERED for Success? You know it's happening within your organization. Employees, armed with cheap and accessible technology, are connecting with customers and building innovative new solutions. But who are these creative problem-solvers? How can you be one? How can you lead them? We call them HEROes: highly empowered and resourceful operatives. HEROes are becoming a critical force for innovation. And you need them now. Armed with a growing torrent of Web information - not to mention iPhones, Facebook, YouTube, and Twitter - your customers have the ability to overmatch your firm. Only HEROes can solve their problems. In Empowered, Forrester's Josh Bernoff - coauthor of Groundswell - and Ted Schadler explain how to transform your company by unleashing the force of these HEROes. Like John Bernier and Ben Hedrington at Best Buy, who built an army of 2,500 tweeting employees to reach out to customers online. Or Ross Inglis, who tapped into Internet computing resources to open a new customer channel for Thomson Reuters. The truth is, one in three of your information workers already use easily accessible technologies that the company does not sanction. Empowered gives you a prescription for embracing this covert innovation and turning it into a boon for the organization. At the heart of a HERO-powered business is a new pact between these critical employees, company managers, and the IT department: HEROes build new solutions to meet customer needs, management sets clear rules while encouraging more experimentation, and IT expands its role to support and secure these business solutions. Fueled by data and analysis from Forrester Research, Empowered offers the business tools and information necessary to move your organization steps ahead of the competition. The reality is that your employees are transforming the way you do business - you can lead them or block them. Empowered will help you make the right decision.
Keywords: Marketing